PENERAPAN GENDER TERHADAP GAYA KEPEMIMPINAN TERKAIT RESULT CONTROL DAN PROCESS CONTROL DI RUMAH MAKAN X - Eugenia Rafella Chrispi (CALYPTRA, 2018)
This study is to determine the role of gender in MCS and leadership style by finding out how the leadership style is applied, then be associated with gender roles and their impact on the result control and process control, the research was conducted in restaurant X. This research is based on the issue that women tend to have a feminine leadership style and men tend to have a masculine leadership style. The results of the study found Ms. Brenda prefer masculine character but also support the existence of feminine character that impact on assertiveness in process control and the result of result control.